2014
DOI: 10.2139/ssrn.2459530
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Unconventional Monetary Policy and Transmission to Emerging Market Economies

Abstract: We investigate the effects of U.S. unconventional monetary policies on sovereign yields, foreign exchange rates, and stock prices in emerging market economies (EMEs), and we analyze how these effects depend on country-specific characteristics. We find that, although EME asset prices, mainly those of sovereign bonds, responded strongly to unconventional monetary policy announcements, these responses were not outsized with respect to a model that takes into account each country's time-varying vulnerability to U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Following a "taper tantrum" in mid-2013, which raised concerns about the normalization of US monetary policy, academic interest on the effect of US monetary policy on emerging economies has been increasing. Bowman, Londono, and Spariza (2014) use VAR and event study to examine the determinants of EMEs' vulnerability to UMP. 9 They find that the (Federal 7 However, expansionary monetary policy shock did not raise stock prices in the United Kingdom and Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a "taper tantrum" in mid-2013, which raised concerns about the normalization of US monetary policy, academic interest on the effect of US monetary policy on emerging economies has been increasing. Bowman, Londono, and Spariza (2014) use VAR and event study to examine the determinants of EMEs' vulnerability to UMP. 9 They find that the (Federal 7 However, expansionary monetary policy shock did not raise stock prices in the United Kingdom and Japan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They choose November 25, 2008, December 1, 2008, December 16, 2008, January 28, 2009, and March 18, 2009 for QE1; August 10, 2010, September 21, 2010, and October 15, 2010 for QE2; and September 21, 2011 for OT. In addition to these dates, we add the dates of QE3, tapering off, and forward guidance, based on Chen, Griffoli, and Sahay (2014), Bowman, Londono, and Spariza (2014), Federal Open Market Committee (FOMC) minutes, and informal talks with bond market participants. We use May 22, 2013 and June 19, 2013 for the dates of tapering.…”
Section: Dates Of Ump-related Newsmentioning
confidence: 99%
“…For example, Eichengreen and Gupta (2014) analyze the effects of "tapering talk" on the macroeconomic variables of emerging markets. Bowman, Londono, and Sapriza (2014) explore how the FRB's unconventional monetary policy affected the emerging market economies' asset prices as well as their capital flows. Lim, Mohapatra, and Stocker (2014) focus mostly on the effects of the unconventional monetary policies of high-income economies on the financial inflows to developing economies, and simulate the effect of monetary policy normalization.…”
Section: A Objectives Of Analysismentioning
confidence: 99%
“…Among unconventional policies in advanced countries, a number of studies suggested that a highly accommodative monetary policy in the United States has created major challenges for policymakers in the rest of the world, especially in emerging market economies (EMEs) (see, for example, Fratzscher, Lo Duca, and Straub [2013]; Chen, Mancini-Griffoli, and Sahay [2014]; Bowman, Londono, and Sapriza [2014]; Neely [2015]). Quite a few EMEs experienced rapid capital inflows and strong currency-appreciation pressures during 2010-12 while they saw a sharp reversal in episodes of market volatility after the Federal Reserve Board's (FRB) Chairman Bernanke's tapering comments on May 22, 2013.…”
Section: Introductionmentioning
confidence: 99%